2019
DOI: 10.22161/ijeab/4.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Textile dyes by Fungal-Bacterial Biofilms

Abstract: Textile waste pollutants are the most polluting waste water and their treatment is greatly challenging for their safe discard. Microbial communities have potential ability to decolorize synthetic commercial dyes used for textile dyeing. Therefore, this study was aimed to develop potential dye degrading microbial biofilms from endophytic fungi and soil bacteria. Endophytic fungi were isolated from the leaves of Eleusine indica (Linn) and bacteria were isolated from soil samples obtained near textile effluent du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Comparing fungal–bacterial biofilms to their individual cultures, Nigrosin disodium and Malachite Green dyes are more effectively degraded. In this experiment, Trichoderma harzianum , Pseudomonas fluorescens , and Bacillus subtilis produced a biofilm that had the highest dye removal ability for both Nigrosin disodium and Malachite Green dyes ( Henagamage, 2019 ). Biofilm consortiums were also useful in the color removal, degradation, and detoxification of the azo dye Methyl Orange ( Haque et al, 2021 ).…”
Section: Recent Strategies For Pollutants Remediationmentioning
confidence: 99%
“…Comparing fungal–bacterial biofilms to their individual cultures, Nigrosin disodium and Malachite Green dyes are more effectively degraded. In this experiment, Trichoderma harzianum , Pseudomonas fluorescens , and Bacillus subtilis produced a biofilm that had the highest dye removal ability for both Nigrosin disodium and Malachite Green dyes ( Henagamage, 2019 ). Biofilm consortiums were also useful in the color removal, degradation, and detoxification of the azo dye Methyl Orange ( Haque et al, 2021 ).…”
Section: Recent Strategies For Pollutants Remediationmentioning
confidence: 99%
“…For the Navy Blue FB, they found the maximum decolorization activity of the isolated fungal strain under static condition at pH 6.0, 27°C and within 3-4 days of incubation period (Arya, 2019). Henagamage (2019) developed microbial biofilms (fungal-bacterial biofilms) using endophytic fungi and soil bacteria for the bioremediation of textile dyes and concluded that for the treatment of textile effluents, biofilms may be applied as efficient biological tools. In comparison to monocultures, Malachite green and Nigrosin disodium dyes were greatly degradable with fungal bacterial biofilms and for both dyes, highest dye reduction ability was shown by the biofilm combination Tricoderma harzianum, Bacillus subtilis, and Pseudomonas fluorescens (Henagamage, 2019).…”
Section: Mycoremediation Of Dyesmentioning
confidence: 99%
“…Henagamage (2019) developed microbial biofilms (fungal‐bacterial biofilms) using endophytic fungi and soil bacteria for the bioremediation of textile dyes and concluded that for the treatment of textile effluents, biofilms may be applied as efficient biological tools. In comparison to monocultures, Malachite green and Nigrosin disodium dyes were greatly degradable with fungal bacterial biofilms and for both dyes, highest dye reduction ability was shown by the biofilm combination Tricoderma harzianum, Bacillus subtilis , and Pseudomonas fluorescens (Henagamage, 2019). Study on the mycoremediation of dyes is not limited to the above demonstrated works.…”
Section: Mycoremediation Of Organic Pollutantsmentioning
confidence: 99%
“…Many toxic dyes cause soil and water pollution and are serious issues that need immediate solutions (Henagamage, 2019). The toxic dyes include azo dyes, acid orange, acid red, solvent red, etc.…”
Section: Introductionmentioning
confidence: 99%